Ação e (des) motivação do professor de geografia: a prática docente do professor de geografia no ensino fundamental - Pereira, Ádria Messias (2008)
The aim of this work is to understand the conception of Geography teachers of the municipal schools of the south region of Goiânia on motivation, as well as understand their motivations during their lectures. Therefore it is a research on the conceptions and motivations of Geography teachers. 14 (Fourteen) teachers, graduated in Geography, from the municipal schools of the south region of Goiânia, participated on this study on the first stage, answering a questionnaire in order to understand their conception of motivation, and then five among these teachers were selected to participate on the second stage, which is a semi-structured interview that aims to investigate their motivations during their classes. At a first moment, a bibliographic review was done on motivation as a current issue among Geography teachers, being the basis to the research Vigotsky and his followers. At second, a bibliographic review was taken from the main issues of the teachers who responded the questionnaire and were interviewed, such as The Geography Education, the current contributions of the Practice of Teaching, the identity of teachers, as well as their continued education and the motivation contributions for the teaching practice. At third, a brief presentation of the South Region of Goiânia was done with the intent to better comprehend the reality where the participant teachers act, and then the answers to the questionnaire are discussed in relation to their conceptions of motivation. And at forth, in order to approach the theory of motivation or non motivation of the Geography teacher, their motivations were analyzed. This work highlights the need for the increase of the value of the Geography teacher motivation during their practice as the public institution’s concern, the University’s and all its own components of the school context. Therefore to reach a better comprehension of Goiania’s formal education current context it is essential that the teachers’ motivations be considered. The better the understanding of the emotions of the educators, the bigger is the unveiling of the fan of human possibilities during the teaching-learning process.